Metabolomics analysis reveals enhanced salt tolerance in maize through exogenous Valine-Threonine-Isoleucine-Aspartic acid application - Wu, Kaihua; Liang, Xiaoyan; Zhang, Xiu; Yang, Guoping; Wang, Huaxiao; Xia, Yining; Ishfaq, Shumila; Ji, Hongfei; Qi, Yuxi; Guo, Wei (Frontiers in Plant Science, 2024)
Salt stress is a well-known abiotic constraint that hampers crop productivity, affecting more than 424 million hectares of topsoil worldwide. Applying plant growth regulators externally has proven effective in enhancing crop resilience to salt stress. Previous metabolomics studies revealed an accumulation of Valine-Threonine-Isoleucine-Aspartic acid (VTID) in salt-stressed maize seedlings, suggesting its potential to assist maize adaptation to salt stress. To explore the effectiveness of VTID in enhancing salt tolerance in maize, 10 nM VTID was applied to salt-stressed maize seedlings. The results showed a remarkable 152.29% increase in plant height and a 122.40% increase in fresh weight compared to salt-stressed seedlings. Moreover, the addition of VTID enhanced the activity of antioxidant enzymes, specifically superoxide dismutase (SOD) and catalase (CAT), while reducing the level of malondialdehyde (MDA), a marker of oxidative stress. Additionally, VTID supplementation resulted in a significant increase in osmoregulatory substances such as proline. Metabolomic analysis revealed substantial changes in the metabolite profile of maize seedlings when treated with VTID during salt stress. Differential metabolites (DMs) analysis revealed that the identified DMs primarily belonged to lipids and lipid-like molecules. The receiver operating characteristic curve and linear regression analysis determined a correlation between isodolichantoside and the height of maize seedlings under salt-stress conditions. In conclusion, these findings validate that VTID effectively regulates tolerance in maize seedlings and offers valuable insights into the potential of short peptides for mitigating salt stress.